Drunken Language, Elliptical Politics: Caryl Churchill’s Oblique Protest Theatre - Jones, Matt (Analyses/Rereadings/Theories: A Journal Devoted to Literature, Film and Theatre, 2019)
Can “political theatre” exist in today’s political climate? In the last few decades, our understanding of politics and theatre has undermined the basis on which prior generations of artists conceived of both politics and theatre. Caryl Churchill’s Drunk Enough to Say I Love You? sits at the intersection of critiques of dramatic theatre and new forms of post-dramatic, non-representational performance. The play tells the story of a man, Guy, who falls in love with a country, Sam, and critics have largely seen the play as an allegory for the “special relationship” between Britain and the United States. But while the play riffs on that metaphor, it also includes aspects that work against a political reading. Churchill’s depiction of the relationship as a sincere gay love affair raises questions about what it means to say that politicians are “in bed together.” As the play develops, the political critique and the personal relationships seem to work against each other, and the play becomes an elliptical invitation to think political theatre anew.